A qualitative case study for the planning and implementation of post-conflict reconstruction projects in Kosovo - Earnest, James; Dickie, Carolyn (Australian and New Zealand Academy of Management, 2012)
Post-conflict reconstruction more so than any other development trajectory, must be underpinned by institutions capable of facilitating the transition from war to sustainable peace. It must also lay the groundwork for the physical, social and economic recovery of communities by adapting a comprehensive, well-sequenced and flexible approach. Knowledge of key elements and challenges for developing economic rehabilitation and reconstruction projects in long-term development strategies for post-conflict governance structures need to be identified. Much remains to be learned about the planning and implementation of reconstruction and development projects by the international/local community to make international donor assistance in conflict-related situations more effective. The study elaborates on the concept of the project delivery process, planning, implementation and monitoring in post-conflict settings.